Risk-Contingent Credit (RCC): Assessing smallholders' agricultural credit needs and the feasibility of implementing RCC in Ethiopia - Timu, Anne G.; Shee, Apurba; Yilma, Marta; Bellisa, Temesgen; Kebede, Temesgen; You, Liangzhi (International Food Policy Research Institute, 2023)
Agricultural credit is an important instrument for improving farm productivity, the welfare of farm households, and their resilience to weather-related shocks. However, small-scale farmers’ access to credit is limited by demand- and supply-side constraints. Risk-contingent credit, which bundles credit with insurance against climate risks, is one promising solution. This study, conducted in three woredas in Ethiopia, implemented a game designed to increased farmers’ understanding of the product and finds that farmers recognize the potential of RCC.